Performance Evaluation on Low-Crest Breakwater at North Coast of Java Island - Parlindungan Sudrajat Simanjuntak (Journal of the Civil Engineering Forum, 2018)
Low-crest breakwater is one of coastal safety structures that used in managing the erosion at along the coast. As a newly studied and used coastal safety structure in Indonesia, the use of the structure requires an evaluation of whether its application is succeeded or not. Therefore, evaluation regarding on the utilization of coastal safety structure in form of low-crest breakwater was conducted. The research was to be conducted in locations that have low-crest breakwater structures, which is Pekalongan City, Demak Regency, and Jepara Regency. The research was conducted by using primary data in form of direct observation on location of implementation; and secondary data in form of tidal, wave, and coast material data. These data were expected to be able to provide a depiction on whether the low-crest breakwater structure application in Pekalongan City, Demak Regency, and Jepara Regency are succeeded. The observation in the implementation area showed positive result in the form of coast sedimentation in Pekalongan City and Demak Regency; although structural damage occurred in the Jepara Regency location. The matters that related to this condition were structure material and coast utilization. The material of the structured use geo-textile with 5 to 7 years usage time—in which damage would develop when in direct contact with human or if there’s sharp material towards the coast. In the case of coast utilization activities, such as boat mooring or fishing, geotextile material best not to be installed, or other stronger material should be chosen for it.